GAMBARAN PERILAKU DAN PENGATURAN PENGGUNAAN TELEPON GENGGAM CERDAS (TGC) PADA SISWA SEKOLAH MENENGAH KEJURUAN - Tji Beng Jap; Hartinah Dinata; Vivien H. Wangi; Sri Tiatri (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2021)
Smartphone are tools that help life, even become daily needs for adolescents in Vocational High School (Sekolah Menengah Kejuruan or SMK) who live in urban areas. Unfortunately, not a few teenagers experience problems due to excessive smartphone use. These can include physical problems such as problems with the eyes, movement, and body position; as well as psychological problems such as unharmonious relationships with the people around them, or feeling dependent on devices. There are not many studies that describe the behavior and regulation of smartphone use in adolescents, especially vocational high school students in Indonesia. This study aims to obtain a description of the behavior of smartphone use among vocational high school students, as well as the settings up of regulations by the home and school environment. Participants are 1.921 high school students in 5 cities in 5 provinces in Indonesia (West Kalimantan, Yogyakarta Special Region (DIY), Bangka Belitung Islands, North Sulawesi, and Central Java). Data collection was carried out through a survey with a questionnaire specially designed by the researcher. Data collection was carried out before the COVID-19 Pandemic occurred. The results showed that in the period before the COVID-19 Pandemic, most students used smartphones for about 4-8 hours per day, for communication purposes. In addition, parents and schools make regulations regarding the use of smartphones. The results of this study can provide an overview, as well as a comparison for the description of the behavior of device use after the outbreak of the COVID-19 outbreak. Telepon Genggam Cerdas (TGC) merupakan alat yang membantu kehidupan, bahkan menjadi kebutuhan sehari-hari bagi remaja di Sekolah Menengah Kejuruan (SMK) yang tinggal di daerah perkotaan. Sayangnya, tidak sedikit remaja yang mengalami masalah akibat penggunaan TGC yang berlebihan. Masalah itu dapat berupa masalah fisik seperti masalah pada mata, pergerakan, dan posisi tubuh; maupun masalah psikologis seperti hubungan yang kurang harmonis dengan orang-orang disekitarnya, atau merasakan ketergantungan terhadap gawai. Belum banyak studi yang menggambarkan perilaku dan pengaturan penggunaan TGC pada remaja khususnya siswa SMK. Penelitian ini bertujuan mendapatkan gambaran perilaku penggunaan gawai pada siswa SMK, serta pengaturan yang ditetapkan oleh lingkungan rumah dan sekolah. Partisipan adalah 1921 siswa SMK di 5 kota yang ada di 5 provinsi di Indonesia (Kalimantan Barat, Daerah Istimewa Yogyakarta (DIY), Kepulauan Bangka Belitung, Sulawesi Utara, dan Jawa Tengah). Pengumpulan data dilaksanakan melalui survei dengan kuesioner yang dirancang khusus oleh peneliti. Pengambilan data dilaksanakan sebelum terjadinya Pandemi COVID-19. Hasil penelitian menunjukkan bahwa pada masa sebelum Pandemi COVID-19, kebanyakan siswa menggunakan TGC selama sekitar 4-8 jam per-hari, untuk keperluan berkomunikasi. Selain itu, orang tua dan sekolah membuat aturan mengenai penggunaan TGC. Hasil penelitian ini dapat memberikan gambaran, sekaligus pembanding bagi gambaran perilaku penggunaan gawai sesudah merebaknya wabah COVID-19.